Major shifts in gut microbiota during development and its relationship to growth in ostriches - Elin Videvall; Se Jin Song; Hanna M. Bensch; Maria Strandh; Anel Engelbrecht; Naomi Serfontein; Olof Hellgren; Adriaan Olivier; Schalk Cloete; Rob Knight; Charlie K. Cornwallis (Molecular Ecology, 2019)
The development of gut microbiota during ontogeny is emerging as an important process influencing physiology, immunity and fitness in vertebrates. However, knowledge of how bacteria colonize the juvenile gut, how this is influenced by changes in the diversity of gut bacteria and to what extent this influences host fitness, particularly in nonmodel organisms, is lacking. Here we used 16S rRNA gene sequencing to describe the successional development of the faecal microbiome in ostriches ( Struthio camelus , n = 66, repeatedly sampled) over the first 3 months of life and its relationship to growth. We found a gradual increase in microbial diversity with age that involved multiple colonization and extinction events and a major taxonomic shift in bacteria that coincided with the cessation of yolk absorption. Comparisons with the microbiota of adults ( n = 5) revealed that the chicks became more similar in their microbial diversity and composition to adults as they aged. There was a five‐fold difference in juvenile growth during development, and growth during the first week of age was strongly positively correlated with the abundance of the genus Bacteroides and negatively correlated with Akkermansia. After the first week, the abundances of six phylogenetically diverse families (Peptococcaceae, S24‐7, Verrucomicrobiae, Anaeroplasmataceae, Streptococcaceae, Methanobacteriaceae) were associated with subsequent reductions in chick growth in an age‐specific and transient manner. These results have broad implications for our understanding of the development of gut microbiota and its associations with animal growth.

Plumage microbiota covaries with the major histocompatibility complex in blue petrels - Sarah Leclaire; Maria Strandh; Gaia Dell’Ariccia; Marianne Gabirot; Helena Westerdahl; Francesco Bonadonna (Molecular Ecology, 2019)
To increase fitness, a wide range of vertebrates preferentially mate with partners that are dissimilar at the major histocompatibility complex (MHC) or that have high MHC diversity. Although MHC often can be assessed through olfactory cues, the mechanism by which MHC genes influence odour remains largely unclear. MHC class IIB molecules, which enable recognition and elimination of extracellular bacteria, have been suggested to influence odour indirectly by shaping odour‐producing microbiota, i.e. bacterial communities. However, there is little evidence of the predicted covariation between an animal's MHC genotype and its bacterial communities in scent‐producing body surfaces. Here, using high‐throughput sequencing, we tested the covariation between MHC class IIB genotypes and feather microbiota in the blue petrel ( Halobaena caerulea ), a seabird with highly developed olfaction that has been suggested to rely on oduor cues during an MHC‐based mate choice. First, we show that individuals with similar MHC class IIB profiles also have similar bacterial assemblages in their feathers. Then, we show that individuals with high MHC diversity have less diverse feather microbiota and also a reduced abundance of a bacterium of the genus Arsenophonus , a genus in which some species are symbionts of avian ectoparasites. Our results, showing that feather microbiota covary with MHC, are consistent with the hypothesis that individual MHC genotype may shape the semiochemical‐producing microbiota in birds.

Characterization of MHC class I and II genes in a subantarctic seabird, the blue petrel, Halobaena caerulea (Procellariiformes) - Maria Strandh; Mimi Lannefors; Francesco Bonadonna; Helena Westerdahl (Immunogenetics, 2011)